2004
DOI: 10.1016/s0002-9440(10)63318-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Switch from Paracrine to Autocrine Role of Hepatocyte Growth Factor in an Androgen-Independent Human Prostatic Carcinoma Cell Line, CWR22R

Abstract: Support mechanisms involved in growth of androgen-independent prostate cancer are primarily unknown. Hepatocyte growth factor (HGF)/Met has been suggested to be one of them based primarily on immunohistochemical studies. We conducted a series of experiments to assess the role of the HGF/Met system in an androgen-dependent human prostate carcinoma, CWR22 and its androgen-independent derivative, CWR22R. We found that action of HGF changed from paracrine to autocrine in progression to androgen-independent state. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
(40 reference statements)
3
35
0
Order By: Relevance
“…Interestingly, we only observed a slight effect on c-Met expression by the AR shRNA in CWR22Rv1 cells. In addition, a higher level of cMet expression in CWR22Rv.1 cell line than its parental line CWR22 had been reported (42). In transient transfection experiments, we also observed that increasing expression of Sp1 proteins ectopically in prostate cancer cells can attenuate the repressive effect of AR on c-Met expression (data not shown).…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, we only observed a slight effect on c-Met expression by the AR shRNA in CWR22Rv1 cells. In addition, a higher level of cMet expression in CWR22Rv.1 cell line than its parental line CWR22 had been reported (42). In transient transfection experiments, we also observed that increasing expression of Sp1 proteins ectopically in prostate cancer cells can attenuate the repressive effect of AR on c-Met expression (data not shown).…”
Section: Discussionsupporting
confidence: 59%
“…How such constitutive c-Met activation is acquired remains elusive. In some studies, the existence of a HGF/c-Met autocrine loop has been suggested (36,38), but others indicate that PC-3 cells do not express HGF (16,39). Clearly, elucidating the mechanism of c-Met activation in the absence of exogenous ligand in the PC-3 model would provide important information about the potential therapeutic application of Met inhibitors in cancer patients whose tumors possess cells with constitutively activated c-Met.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the recent studies demonstrating that active hepsin can catalyze the conversion of pro-HGF to the c-met binding ligand, HGF (27,28), as confirmed here using the modified activated hepsin protein, point to a possible role for hepsin in the activation of tumorpromoting factors. There is considerable evidence that c-met and HGF are involved in metastatic prostate cancer (30), and development of an autocrine loop for HGF/c-met has been proposed as one of the mechanisms leading to androgenindependent tumors (31). The coexpression of hepsin with HGF and c-met in metastatic cancers may be key in the activation of the HGF/c-met pathway in late stage prostate tumors.…”
Section: Discussionmentioning
confidence: 99%